Implementasi ‘Amaliyah al-Tadris dalam Pendidikan Islam: Upaya Pengembangan Kompetensi Pedagogik dan Profesional Peserta Didik Madrasah Aliyah: Implementation of ‘Amaliyah al-Tadris in Islamic Education: Developing Pedagogical and Professional Competencies of Madrasah Aliyah Students - Mega Safita Putri Mega Safita; Muhammad Ilman Hafizhul Huda (Prodi PAI, Fakultas Tarbiyah, UNIDA GONTORs Tarbiyah, Universitas Darussalam Gontor, 2026)
Teachers play a vital role in the learning process; however, many still face challenges in managing instruction, which affects their pedagogical competence and professional performance. This condition indicates the need for a structured preparatory program for prospective teachers that integrates theoretical understanding with practical teaching experience. The ‘Amaliyah Al-Tadris program implemented at MA Sulamul Huda Siwalan serves as a systematic effort to prepare twelfth-grade students to become competent and professional teachers through guided teaching practice grounded in Islamic educational values. This study aims to describe the implementation of the ‘Amaliyah Al-Tadris program and to analyze its role in developing students’ pedagogical and professional competencies. The research employed a qualitative approach with a case study design. Data were collected through participatory observation, in-depth interviews, and documentation, and analyzed using the Miles, Huberman, and Saldana interactive model. The findings reveal that the program is conducted in three stages: cognitive preparation, teaching practice, and evaluation (naqd). The program contributes positively to the development of students’ pedagogical competence, including lesson planning, the implementation of educative and dialogic learning, and the assessment of learning outcomes. Furthermore, it strengthens students’ professional competence through mastery of subject matter, the use of instructional media and learning resources, and an understanding of the foundations of Islamic education. The study concludes that the ‘Amaliyah Al-Tadris program plays a significant role in preparing prospective teachers with strong pedagogical and professional competencies within the context of Islamic education.